ANALISIS PENERAPAN ACTIVITY BASED COSTING SYSTEM DALAM MENENTUKAN HARGA POKOK KAMAR - Syarifudin, Akhmad (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
Hotel Cadaka in calculating the cost of the product is still using the traditional method, while in traditional cost accounting system charges made on the production of direct and indirect costs associated with the product. As a result the cost of the product will appear below the cost price and the cost of the product above the base price. Activity based costing system is a method that is designed to rectify the shortcomings of traditional methods due to the activity based costing system products or services performed by the activity, and the activities required the use of resources that causes the cost. The objective of this study was to determine the room rates that more accurately by using the ABC method System and to compare the magnitude of the cost of the room by using the traditional method of activity based costing method at Hotel Cadaka Gombong. The results of calculating the cost of the room by using traditional methods to the VIP room 268,403,28, Family AC 247,778.07, Family 206,382.17, Superior AC 165,153.68, Superior 165,171.67, Standard 103,206.40, Economy 82594.51. While the results of calculating the cost of the room by using activity based costing system for VIP room 205,305.65, Family AC 202,911.88, Family 195,503.18, Superior AC 170,842.96, Superior 183,380.06, Standard 188,692,23 and Economy 185,874.00 , This is because the overhead charges on each product is charged to a lot of cost driver. So in activity based costing, able to allocate activity costs to each room and accurately based on the consumption of each activity. So that can assist management in controlling costs better.   Keywords : Cost of Production , Traditional System , Activity Based Costing System